Add-back medrogestone does not prevent bone loss in premenopausal women treated with goserelin - Sillem, Martin; Parviz, Maryam; Woitge, Henning W.; Kiesel, L.; Ulrich, U.; Holst, Thomas von; Runnebaum, Benno; Ziegler, Reinhard; Seibel, Markus J. (Experimental and clinical endocrinology & diabetes, 1999)
To investigate the effect of medrogestone on bone mineral density (BMD) and bone turnover under conditions of estrogen withdrawal, premenopausal women with endometriosis were treated with goserelin (Zoladex®), combined with either placebo (group A, n = 12) or 10 mg medrogestone (Prothil®, group B, n = 11) for six months, and followed for an additional six months. Lumbar spine BMD was measured at 0 and 6 month. Markers of bone turnover were serum bone alkaline phosphatase (sBAP) and osteocalcin (sOC) by ELISA, and urinary total pyridinoline (uPYD) and deoxypyridinoline crosslinks (uDPD) by HPLC.